Uji Keamanan Cemaran pada MP-ASI Berbahan Kedelai Kulit Buah Naga - Olivia, Zora; Rosiana, Nita Maria; Suryana, Arinda Lironika; Widiyawati, Agatha (Puslitbang Sinergis Asa Professional, 2025)
Complementary feeding is nutritious food in addition to breast milk given to infants during the complementary feeding period to achieve nutritional adequacy. Complementary feeding products to be marketed should be guaranteed to be safe from metal and microbial contamination. SNI 01-7111.1-2005 explains the minimum limits for contamination of arsenic, lead, tin, mercury and free from Escherichia coli, Salmonella sp, Staphylococcus aureus microbes. This study aims to determine safety by comparing the metal contamination and microbial contamination figures between the P1, P2 and P3 complementary feeding formulas. P1 and P2 are complementary feeding made from soybean powder and dragon fruit skin. P1 consists of 25% soybean powder, 45% powdered milk, 10% dragon fruit skin powder, 20% sugar. P2 consists of 35% soybean powder, 35% powdered milk, 10% dragon fruit skin powder, 20% sugar. While P3 is a commercial complementary feeding. The methods used for metal contamination detection are ICP-MS, coliform and Escherichia coli microbial contamination with the Most Probable Number (Apm) technique and APL with the pour plate technique, detection of salmonella spp. according to ISO 6579-1: 2017, Positive Coagulation Staphylococci. The results include arsenic metal contamination in P2 and P3 while lead in P2 with levels below the maximum SNI limit. Microbial contamination ALT, Escherichia coli, Salmonella sp, Staphylococcus aureus. P1, P2, P3 according to SNI standards while coliform only in P2 meets SNI standards. So it can be concluded that the MPASI formula from soybean powder and dragon fruit skin P2 is the safest to consume because it has metal and microbial contamination results according to SNI standards.